Seed Deterioration: An Overview - VIDYA CJ; N NETHRA (Seed Research, 2026)
Seed deterioration represents an undesirable facet of seed life, characterized by degenerative changes over time that heighten a seed’s susceptibility to external stressors while diminishing its capacity to endure external and internal stresses. This phenomenon is distinct from seed expansion and germination, manifested during field weathering, harvesting, and storage. The intricacies of seed physiology and diverse conditions during the lifespan of the seed contribute to this deterioration. Investigations into seed deterioration reveal profound consequences on various physiological aspects within a normally functioning cell. Lipid peroxidation, membrane disruption, encompassing the degradation of DNA and RNA, impairment of transcription and translation processes, increased permeability of the cellular membranes, alterations in carbohydrate reserves, and antioxidant shifts contribute to the overall seed deterioration. Predominant evidences implicate free radical peroxidative assaults on membrane lipids as the instigator of many of these deteriorative events. Evaluation of seed deterioration conventionally relies on vigor and viability tests, such as germination, electrical conductivity (EC), performance tests, and ethanol assays. Modern technologies offer precise, or non-destructive and expeditious alternatives for assessing seed deterioration and quality. These include advanced spectroscopic techniques like FT-NIR and Raman spectroscopy, digital imaging, soft X-Ray imaging, and molecular marker-based tests.